Only zeta this time

Calculus Level 5

n = 1 ( ζ ( 2 ) 1 1 2 2 1 n 2 ) 2 = a ζ ( k ) b c ζ ( m ) d \sum_{n=1}^{\infty}\left(\zeta(2)- 1 - \frac{1}{2^2} - \dots - \frac{1}{n^2}\right)^2= \frac{a \zeta(k) }{b} - \frac{c\zeta(m)}{d}

The above equation is satisfied, where ζ \zeta is the Riemann zeta function and a , b , c , d , k , m a,b,c,d,k,m are positive integers and gcd ( a , b ) = gcd ( c , d ) = 1 \gcd(a,b)=\gcd(c,d)=1 , what is a + b + c + d + k + m ? a+b+c+d+k+m?


The answer is 18.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hamza A
Apr 25, 2016

We have, by Abel's summation formula,that n = 1 ( ζ ( 2 ) 1 1 2 2 1 n 2 ) 2 = 2 n = 1 n ( n + 1 ) 2 ( ζ ( 2 ) H n ( 2 ) ) n = 1 n ( n + 1 ) 4 = 2 n = 1 1 n + 1 ( ζ ( 2 ) H n ( 2 ) ) 2 n = 1 1 ( n + 1 ) 2 ( ζ ( 2 ) H n ( 2 ) ) ζ ( 3 ) + ζ ( 4 ) \sum_{n=1}^{\infty}\left(\zeta(2)- 1 - \frac{1}{2^2} - \dots - \frac{1}{n^2}\right)^2= \\2\sum _{ n=1 }^{ \infty }{ \frac { n }{ (n+1)^{ 2 } } \left( \zeta (2)-{ H }_{ n }^{ (2) } \right) } -\sum _{ n=1 }^{ \infty }{ \frac { n }{ (n+1)^{ 4 } } }=\\2\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ n+1 } \left( \zeta (2)-{ H }_{ n }^{ (2) } \right) } -2\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ (n+1)^{ 2 } } \left( \zeta (2)-{ H }_{ n }^{ (2) } \right) } -\zeta (3)+\zeta (4)

in order to find the value of the first sum,we need the following lemma

Lemma : n = 1 1 n ( ζ ( 2 ) H n ( 2 ) ) = ζ ( 3 ) \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ n } \left( \zeta (2)-{ H }_{ n }^{ (2) } \right) } =\zeta (3)

Proof :

We apply Abel's summation formula and we get that n = 1 1 n ( ζ ( 2 ) H n ( 2 ) ) = lim n H n ( ζ ( 2 ) H n + 1 ( 2 ) ) + n = 1 H n ( n + 1 ) 2 = n = 1 ( H n + 1 ( n + 1 ) 2 1 ( n + 1 ) 3 ) = ζ ( 3 ) \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ n } \left( \zeta (2)-{ H }_{ n }^{ (2) } \right) } =\lim _{ n\rightarrow \infty }{ { H }_{ n }\left( \zeta (2)-{ H }_{ n+1 }^{ (2) } \right) } +\sum _{ n=1 }^{ \infty }{ \frac { { H }_{ n } }{ { (n+1) }^{ 2 } } } =\\ \sum _{ n=1 }^{ \infty }{ \left( \frac { { H }_{ n+1 } }{ { (n+1) }^{ 2 } } -\frac { 1 }{ (n+1)^{ 3 } } \right) } =\zeta (3)


we used that n = 1 H n n 2 = 2 ζ ( 3 ) \sum _{ n=1 }^{ \infty }{ \frac { { H }_{ n } }{ { n }^{ 2 } } } =2\zeta (3)

the proof is simple and left as an exercise for the reader

Hint: 0 1 x n ln ( 1 x ) = H n + 1 n + 1 \int _{ 0 }^{ 1 }{ { x }^{ n }\ln { (1-x) } } =-\frac { { H }_{ n+1 } }{ n+1 }


back to our solution we have

n = 1 1 n + 1 ( ζ ( 2 ) H n ( 2 ) ) = n = 1 1 n + 1 ( ζ ( 2 ) H n + 1 ( 2 ) ) + n = 1 1 ( n + 1 ) 3 \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ n+1 } \left( \zeta (2)-{ H }_{ n }^{ (2) } \right) }=\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ n+1 } \left( \zeta (2)-{ H }_{ n+1 }^{ (2) } \right) } +\sum _{ n=1 }^{ \infty }{ \frac { 1 }{ (n+1)^{ 3 } } }

using the lemma we get that the sum is equal to 2 ζ ( 3 ) ζ ( 2 ) 2\zeta (3)-\zeta (2)

on the other hand,a calculation shows that n = 1 1 ( n + 1 ) 2 ( ζ ( 2 ) H n ( 2 ) ) = 0 1 ln x x ( 1 x ) ( Li 2 ( x ) x ) \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ (n+1)^{ 2 } } \left( \zeta (2)-{ H }_{ n }^{ (2) } \right) } =-\int _{ 0 }^{ 1 }{ \frac { \ln { x } }{ x(1-x) } \left(\text{Li}_2(x) -x \right) }

evaluating the integral we get 7 4 ζ ( 4 ) ζ ( 2 ) \frac { 7 }{ 4 } \zeta (4)-\zeta (2)

putting all of those together we get the desired sum n = 1 ( ζ ( 2 ) 1 1 2 2 1 n 2 ) 2 = 3 ζ ( 3 ) 5 2 ζ ( 4 ) \sum_{n=1}^{\infty}\left(\zeta(2)- 1 - \frac{1}{2^2} - \dots - \frac{1}{n^2}\right)^2= \Large\boxed{3\zeta (3)-\frac { 5 }{ 2 } \zeta (4)}


Notation used: H n ( s ) = k = 1 n 1 k s { H }_{ n }^{ (s) }=\sum _{ k=1 }^{ n }{ \frac { 1 }{ { k }^{ s } } }

I don't understand the 1st step.

Joe Mansley - 10 months, 3 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...